PENILAIAN TINGKAT KESEHATAN BANK DENGAN METODE RGEC PADA PT. BANK MANDIRI (PERSERO), TBK. - Paramartha, I Made; Darmayanti, Ni Putu Ayu (E-Jurnal Manajemen, 2017)
The level of society’s trust is an absolute thing must be had by every banking corporation. One way of maintaining this trust is by doing an evaluation on bank health level. Bank Indonesia as the central bank of Indonesia has released the regulation about Bank Health Level Evaluation through Peraturan Bank Indonesia No. 13/1/PBI/2011. This evaluation including the method of RGEC (Risk Profile, Good Corporate Governance, Earning, Capital). This research aims to evaluate the level of Mandiri Bank’s health by the RGEC method in the period of 2013-2015. This research is  descriptive research with quantitative approach. The variable risk profile is measured by NPL and LDR ratio. Good Corporate Governance is measured by CAR ratio. The result proves that Bank Mandiri achieve the well health  predicate in the period of 2013-2015. This result shows that Bank Mandiri is capable to deal with negative influence from business condition that may happen.
Keywords: Bank Health Level; Risk Profile; Good Corporate Governance; Earning; Capital.